VD_FINDINFO HC / 2012 / 721 vom 19. November 2012 - VD Tribunal cantonal (2012)
EXPULSION DE LOCATAIRE, DEMEURE, SOMMATION, PROCÉDURE SOMMAIRE | 257d CO, 257 CPC (CH), 308 CPC (CH), 314 al. 1 CPC (CH)